Why do farmers not convert to organic farming? Modeling conversion to organic farming as a major change. (15th May 2018) - Xu, Qing; Huet, Sylvie; Poix, Christophe; Boisdon, Isabelle; Deffuant, Guillaume
Abstract : Abstract: This study aims to better understand why farmers do not convert to organic farming by studying decision trajectories in a dynamic agent‐based model. In this model, an agent's decision on transitioning to organic is based on the comparison between satisfaction with its current situation and potential satisfaction with an alternative farming strategy. A farmer's satisfaction was modeled by borrowing from the Theory of Reasoned Action and computed by comparing the farmer's performance over time against the farming practices of other farmers to which he/she lends great credibility ("important others"). Analysis identified five different reasons why a farmer does not change strategy. Three are due to satisfaction or recovered satisfaction with the current situation. The conversion to organic farming is effectively a major change and cannot be envisaged if the farmer is currently satisfied. Satisfaction can be recovered when evaluation by the farmer or "important others" finds an improvement of the current situation. A farmer's decision to not convert can also be due to negative evaluations of organic farming by "important others, " or to dissatisfaction with the current situation being too transient to prompt the effort to convert. Summary for Managers: A farmer's decision on whether or not to convert to organic farming is deeply influenced by his/her satisfaction with the current strategy and potential satisfaction under an alternative farming strategy. A farmer's satisfaction is computed by comparing the farmer's performance over time against the farming practices of other farmers to which he/she lends great credibility. The conversion to organic farming is effectively a major change, and a farmer will not envisage a change of strategy if he/she is satisfied with their current situation. A farmer's satisfaction can be recovered when evaluation by the farmer or social peers finds an improvement of the current situation. If a farmer's credible peers have a negative assessment of organic farming or if his/her own dissatisfaction with the current situation is too short‐lived, then farmer will not convert to organic farming.